The Book of Ruth and Song of Songs in the First Hebrew Translation of The Taming of the Shrew - Kahn, Lily (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
This article investigates the earliest Hebrew rendition of a Shakespearean comedy, Judah Elkind’s מוסר סוררה musar sorera ‘The Education of the Rebellious Woman’ (The Taming of the Shrew), which was translated directly from the English source text and published in Berditchev in 1892. Elkind’s translation is the only comedy among a small group of pioneering Shakespeare renditions conducted in late nineteenthcentury Eastern Europe by adherents of the Jewish Enlightenment movement. It was rooted in a strongly ideological initiative to establish a modern European-style literature in Hebrew and reflecting Jewish cultural values at a time when the language was still primarily a written medium on the cusp of its large-scale revernacularisation in Palestine. The article examines the ways in which Elkind’s employment of a Judaising translation technique drawing heavily on romantic imagery from prominent biblical intertexts, particularly the Book of Ruth and the Song of Songs, affects the Petruchio and Katherine plotline in the target text. Elkind’s use of carefully selected biblical names for the main characters and his conscious insertion of biblical verses well known in Jewish tradition for their romantic connotations serve to transform Petruchio and Katherine into Peretz and Hoglah, the heroes of a distinctly Jewish love story which offers a unique and intriguing perspective on the translation of Shakespearean comedy.